Arsenic, lead, and cadmium bioaccessibility in contaminated soils: Measurements and validations. Issue 13 (2nd July 2020) - Li, Hong-Bo; Li, Meng-Ya; Zhao, Di; Li, Jie; Li, Shi-Wei; Xiang, Ping; Juhasz, Albert L.; Ma, Lena Q.
Abstract: Ingestion of metal-contaminated soils poses risks to human health. To accurately assess the risks, in vitro assays have been developed to measure metal bioaccessibility. However, they often differ considerably in gastrointestinal fluid components and assay parameters, leading to inconsistent bioaccessibility results. As such, in vitro assays need to be validated against in vivo bioassays based on in vivo-in vitro correlations (IVIVCs). To help researchers to select the best in vitro assay and increase the robustness of the IVIVCs, there is a need to review and compile existing data. In this review, we focus on three metals (As, Pb, and Cd), five common in vitro assays (SBRC, UBM, IVG, DIN, and PBET), and two in vivo bioassays (mouse and swine models). Specifically, we 1) discuss variations in metal bioaccessibility measurements among different in vitro assays, 2) identify the roles of major gastrointestinal fluid constitutes and assay parameters in affecting metal bioaccessibility, 3) summarize weaknesses associated with existing IVIVCs, and 4) establish new IVIVCs using pooled soil samples from different studies. In addition, future research directions are highlighted, including better understanding of the roles of gastrointestinal fluid components, improving in vitro assays to better correlate with in vivo bioassays, expanding bioaccessibility measurements using different in vitro assays, validation of IVIVCs using independent soils, assessing the reliability of in vitro assays in remediated soils, and addressing the mechanisms behind IVIVCs.